The Impact of Lysine and Probiotic Supplementation on Local Artificial Feed Toward Growth, Feed Efficiency, and Survival of Bilih Fish (Rasbora maninjau) - Islama, Dini; Diansyah, Sufal; Samuki, Khairul; S, Irhami; muliyana, Agusriati (Department of Aquaculture, 2025)
Rasbora maninjau is a native fish of Aceh that is commonly found in the rivers of Nagan Raya Regency, West Aceh, Aceh. Although this fish has been domesticated to save it, cultural efforts are severely hampered by its slow growth. Lysine and probiotics are introduced to local feed to maintain the proper balance of amino acids in the feed and improve the quality of the protein feed produced. This makes it possible for the feed to act in a different way to promote the growth of the fish. The purpose of this study is to examine how Rasbora maninjau growth, feed efficiency, and survival are affected by the addition of lysine and probiotics to local feed. A randomized design with three replications and five treatments was used in this study. The formulation uses local feed as a reference (P0), local feed with lysine added at a rate of 1.2% and probiotics at a concentration of 15 ml/kg (P1), 1.4% and probiotics at a concentration of 15 ml/kg (P2), 1.6% and probiotics at a concentration of 15 ml/kg (P3), and 1.8% and probiotics at a concentration of 15 ml/kg (P4). Three times a day, 3% of body weight is fed. The study was raised for 40 days. The findings indicated that adding lysine and probiotics to a locally manufactured meal had a substantial (P < 0.05) effect on Rasbora maninjau's growth performance but had no significant effect on survival (P > 0.05). The best dosages for Rasbora maninjau growth performance in the locally manufactured feed are 1.6% lysine supplementation and 15 ml/kg probiotics (P3).